PATIENTS WITH INTESTINAL INFLAMMATION REQUIRE MORE SEDATION DURING COLONOSCOPY. (8th June 2013) - Kale, V; Dunne, C; Ahmed, M; Lee Chun, S; Cullen, G; Mulcahy, H; Doherty, G
Abstract : Introduction: Colonoscopy is the gold standard for assessing inflammation in the colon and ileum, especially in patients with inflammatory bowel disease (IBD). In the IBD cohort, colonoscopy is of valuable for diagnosing disease, assessing severity, treatment response and identifying complications of the disease (e.g strictures, dysplasia). However, IBD patients are often reluctant to undergo colonoscopy and anecdotally appear to tolerate endoscopy less well than non-IBD patients. Aims/Background: To assess the tolerability of colonoscopy in patients with and without intestinal inflammation by measuring the amount of sedation required and by comparison of the rates of completion and reasons for failed completion. Method: We retrospectively analysed a prospectively maintained endoscopy database in a tertiary referral centre over a four year period from 2009 to 2012. We identified all colonoscopy procedures performed during this period and divided these into two groups depending on the presence or absence of endoscopic evidence of colitis and or ileitis. Data was analysed by Fishers exact test and 2-sample t-test, as appropriate. Results: 954 (9.43%) out of 9000 procedures performed during the timeframe of the study had endoscopic evidence of either colitis and/or ileitis. The mean age in Group 1 (those with colitis and/or ileitis) was 46.6 years. This was significant less than the mean age in Group 2 (those without colitis and/or ileitis) which was 58 years (p<0.001), in line with the younger age profile of IBD. The proportion of females was less in Group 1 (44% versus 53%). Unadjusted completion rates were significantly better in Group 1, (87% Vs 81%, p<0.0001). The mean dose of midazolam used in Group 1 was significantly higher than Group 2, (6.13 mg vs 5.47 mg, p<0.0001). The mean dose of fentanyl required was also significantly higher in Group 1, (70.7mcg Vs 55.5mcg, p<0.0001). There was no significant difference in the need for use of reversal agent (flumazenil) after (0.004% Vs 0.008%, p=0.22). In a multivariate analysis, midazolam dose was positively associated with the presence of intestinal inflammation, independent of patient age and gender (p=0.025). Conclusion: Patient with evidence of intestinal inflammation (colitis and/or ileitis) at the time of colonoscopy require significantly higher doses of sedation and analgesia to facilitate the examination, but are no more likely to require use of reversal agents. These results are consistent with the clinical observation that IBD patients tolerate colonoscopy less well than non-IBD patients and suggest that guidelines on use of sedation during colonoscopy should be tailored to reflect the specific needs of IBD patients, who require endoscopy to be performed frequently as part of their clinical care.